Actinomycetes, promising tools to control plant diseases and to promote plant growth - Doumbou, C.L.; Hamby Salove, M.K.; Crawford, D.L.; Beaulieu, C. (Phytoprotection, 2001)
Actinomycetes represent a high proportion of the soil microbial biomass and have the capacity to produce a wide variety of antibiotics and of extracellular enzymes. Several strains of actinomycetes have been found to protect plants against plant diseases. This review focuses on the potential of actinomycetes as (a) source of agroactive compounds, (b) plant growth promoting organisms, and (c) biocontrol tools of plant diseases. This review also addresses examples of biological control of fungal and bacterial plant pathogens by actinomycetes species which have already reached the market or are likely to be exploited commercially within the next few years.